Utilizing a Recorded-Video to Assess Speaking and Presentation Skills of Pre-Service Teachers - Siane Indriani (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
Teachers have employed in-class oral presentations to practice the pre-service teachers’ speaking skills as they are prepared to become future English teachers who are fluent in communication using English in a globalization era, However, effectively assessing student presentations is challenging, particularly in terms of practical administration of assessment. Therefore, a video recording as an alternative assessment tool was utilized to provide opportunities for learners and their peers to evaluate their speaking and presentation skills. They will need to combine video-camera on their cell phones or tablets and the use e-google form to give immediate feedback for their improvement. The study used a qualitative descriptive method. The data were gathered from the students’ recording videos, reflective journal, feedback from e-google form. The results showed that students got more enthusiastic in presenting their ideas using the video-camera. Furthermore, presentation skills such as the use of eye contact, body posture, and voice were found as other factors that supported the English speaking skills of the pre-service teachers.